Ritual failure in Romans 6 - Smit, Peter-Ben (HTS teologiese studies, 2016)
Ritual studies are slow to make a large impact on New Testament studies, despite a number of notable exceptions. This notwithstanding, rituals occur frequently in the New Testament, in particular when there is a problem with a ritual. In this article, recent anthropological work on ‘ritual failure’ is used to address Paul’s discussion of Roman practices concerning baptism in relation to a person’s walk of life and to argue that this can be understood well as a case of ’ritual failure,’ in which a ritual fails, from Paul’s perspective, to achieve what it should. This leads both to challenging the attitude of the Romans concerning baptism and to a reconsideration of its significance.